KAJIAN KOMPENSASI FINANSIAL LANGSUNG DAN TIDAK LANGSUNG TERHADAP KINERJA KARYAWAN PADA PT. BPR ANUGERAHDHARMA YUWANA BANYUWANGI - Kosdewata, Elly Wahyu; Qomariah, Nurul; WIjayanti, Bayu (Jurnal Sains Manajemen dan Bisnis Indonesia, 2017)
ABSTRACTThis study aims to determine the relationship of financial compensation on employee performance on the PT.BPR ADY Banyuwangi consists of variable Direct Financial Compensation ( X1 ) , Indirect Financial Compensation ( X2 ) significantly both simultaneously and partially on Employee Performance ( Y ) . To find out which of the above variables are the dominant influence on employee performance . The population in this study are employees of PT.BPR ADY Banyuwangi totaling 69 people . The technical  proporsional stratified random sampling . Data collected by distributing questionnaires to the respondents . The scale used is the Likert scale . Results from this study is that simultaneous , variable Direct Financial Compensation ( X1 ) and Indirect Financial Compensation ( X2 ) has a significant influence on employee performance ( Y ) PT.BPR ADY Banyuwangi . Variable Direct Financial Compensation ( X1 ) significantly affects the performance of the employee ( Y ) PT.BPR ADY Banyuwangi . Variable Indirect Financial Compensation ( X2 ) significantly affects the performance of the employee  PT.BPR ADY Banyuwangi . Variable Direct Financial Compensation ( X1 ) has a dominant influence on employee performance ( Y ) PT.BPR ADY Banyuwangi Keywords : financial compensation direct , indirect financial compensation , and employee performance .